FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK DENGAN KESADARAN MEMBAYAR PAJAK SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada UMKM Yang Terdaftar Di Dinas Koperasi Dan UMKM Kabupaten Pati) (Students' Journal of Accounting and Banking, 2014)
This study aims to analyze the influence of knowledge and understanding of tax laws, perception of the effectiveness of the tax system, tax authorities qualified service quality, the level of public confidence in the government and legal system, the perception of good over tax benefits perceived by the willingness to pay taxes, and to analyze whether the awareness of paying taxes is an intervening variable in influencing the willingness to pay taxes on UMKM in Pati.The population in this study are UMKM in Pati. Sampling was done using purposive sampling method and sample size of 100 respondents, consisting of 100 UMKM in Pati. The primary data collection method used was a questionnaire method. analysis of data using multiple linear regression model.The results showed that the knowledge and understanding of tax laws, the perception of the effectiveness of the tax system, the tax authorities qualified service quality and a significant positive effect on the consciousness of paying taxes. The level of confidence in the government and legal system and no significant negative effect on the consciousness of paying taxes. Perception of good over perceived tax benefits and no significant positive effect on the consciousness pay taxes. Awareness paying tax positive effect on the willingness to pay taxes.Keywords : willingness to pay taxes, pay taxes awareness, knowledge and understanding of tax laws, the perception of the effectiveness of the tax system, tax authorities qualified service quality, the level of public confidence in the government and legal system, which is well above the perception of the perceived tax benefits